Feasibility Study of Independent Curriculum Implementation - Radenrara Sutaris (PINISI Discretion Review, 2022)
This research is a design research that aims to obtain an overview of the feasibility of implementing the Independent Curriculum (Indonesia: Implementasi Kurikulum Merdeka / IKM). Feasibility of implementation can be seen from socialization, teacher commitment, learning system, support from school principals, readiness of education units and readiness of infrastructure. The results of the research carried out show that the IKM deserves to reach 74.79% and has a future. The feasibility of each element is 99.1% socialization, 74% teacher commitment, 84.51% learning system, school principal support, education unit readiness and 48% readiness of infrastructure. For the most feasible areas, the Provinces of Yogyakarta, Central Java and Bali are the areas that are most ready to implement IKM, and the provinces that are least ready are North Maluku, Papua. Based on the level, SD level is the most ready and feasible level for IKM implementation, then SMK (Indonesia: Sekolah Menengah Kejuruan), SMA (Indonesia: Sekolah Menengah Atas), SMP (Indonesia: Sekolah Menengah Pertama), SKB (Indonesia: Sanggar Kegiatan Belajar), SLB (Indonesia: Sekolah Luar Biasa) and finally PAUD (Indonesia: Pendidikan Anak Usia Dini).